Private School Culture and Pedagogical Practices: Glance into EWS Children’s Experiences - Kapur, Ashu (Voices of Teachers and Teacher Educators, 2022)
The emerging trend of proliferation of private schooling in India forces to reflect on the confluence of elitist private school culture, teaching-learning discourse and Economically Weaker Section (EWS) or disadvantaged children’s class-cultural conundrums within the school space. It has important implications for tiling the pathway for inclusion of disadvantaged children in the private school ambit, considering the provision in the RTE Act, 2009 for inclusion of 25 per cent children from disadvantaged sections in unaided private schools. This paper is an attempt to interpret the socio-cultural confluence of private school culture, teaching- learning processes and class-cultural specificities embedded in disadvantaged children’s experiences as unravelled in private school setting.